Plant–Microbes Interaction: Exploring the Impact of Cold-Tolerant Bacillus Strains RJGP41 and GBAC46 Volatiles on Tomato Growth Promotion through Different Mechanisms - Abdur Rashid Khan; Qurban Ali; Muhammad Ayaz; Muhammad Saqib Bilal; Taha Majid Mahmood Sheikh; Qin Gu; Huijun Wu; Xuewen Gao (Biology, 2023)
The interaction between plant and bacterial VOCs has been extensively studied, but the role of VOCs in growth promotion still needs to be explored. In the current study, we aim to explore the growth promotion mechanisms of cold-tolerant Bacillus strains GBAC46 and RJGP41 and the well-known PGPR strain FZB42 and their VOCs on tomato plants. The result showed that the activity of phytohormone (IAA) production was greatly improved in GBAC46 and RJGP41 as compared to FZB42 strains. The in vitro and in-pot experiment results showed that the Bacillus VOCs improved plant growth traits in terms of physiological parameters as compared to the CK. The VOCs identified through gas chromatography-mass spectrometry (GC-MS) analysis, namely 2 pentanone, 3-ethyl (2P3E) from GBAC46, 1,3-cyclobutanediol,2,2,4,4-tetramethyl (CBDO) from RJGP41, and benzaldehyde (BDH) from FZB42, were used for plant growth promotion. The results of the partition plate (I-plate) and in-pot experiments showed that all the selected VOCs (2P3E, CBDO, and BDH) promoted plant growth parameters as compared to CK. Furthermore, the root morphological factors also revealed that the selected VOCs improved the root physiological traits in tomato plants. The plant defense enzymes (POD, APX, SOD, and CAT) and total protein contents were studied, and the results showed that the antioxidant enzymes and protein contents significantly increased as compared to CK. Similarly, plant growth promotion expression genes (IAA4, ARF10A, GA2OX2, CKX2, and EXP1) were significantly upregulated and the ERF gene was downregulated as compared to CK. The overall findings suggest that both Bacillus isolates and their pure VOCs positively improved plant growth promotion activities by triggering the antioxidant enzyme activity, protein contents, and relative gene expressions in tomato plants.